Glenoid Reaction to Biocomposite and PEEK Suture Anchors Following Arthroscopic Labral Repairs. Issue 7 (31st July 2020) - Slaven, Sean; Monson, Brett; Aburish, Zein; Kilcoyne, Kelly; LeClere, Lance; Dickens, Jonathan; Colantonio, Donald
Objectives: Biocomposite and all-suture suture anchors have been shown to cause reactive changes in the humerus and glenoid when used for arthroscopic rotator cuff and glenoid labrum repairs. The purpose of this study was to quantify glenoid anchor widening using biocomposite or PEEK suture anchors for arthroscopic shoulder stabilization. Our hypothesis was that biocomposite and PEEK anchors would lead to significant reactive changes in the glenoid as evidenced by a difference in postoperative tunnel size compared to suture anchor diameter. Methods: We searched the Military Data Repository for all patients with a history of a glenoid labrum repair who underwent a postoperative CT scan of the affected shoulder in our hospital market region. CT scans were measured using organic IMPAX tools to calculate the width and length of bone tunnels as described by Tompane et al. Bone mineral density was calculated by measuring the average Hounsfield Units through four axial segments of the glenoid neck in a best fit circle of cancellous bone. Tunnel widening was defined as an increase in width greater than 0.1mm compared to the drill size for each implant. Measurements were made by two independent observers blinded to other patient factors. Patient charts were also reviewed to obtain anchor data, injury, and surgical variables. Univariate analysis was performed to compare differences between tunnel widths and anchor sizes Results: We analyzed 146 bone tunnels in 37 shoulders that met inclusion criteria. The mean age was 23 (18-45), with 126 male and 20 females. The average time to CT scan from labrum repair was 782 days (159-2210). The majority of CT scans (33) were obtained after recurrent instability events, 2 were obtained for preoperative planning prior to shoulder arthroplasty, and 2 were obtained to evaluate the glenoid prior to military commissioning. The average number of anchors used per shoulder was 5. There were 17 PEEK and 129 biocomposite anchors included. There were 113 Arthrex, 28 Mitek, and 3 Zimmer Biomet anchors included in the data. There were 81 anchors in the anterior inferior quadrant, 21 anterior superior, 37 posterior inferior, and 6 in the posterior superior quadrant of the glenoid. The mean difference between tunnel and anchor width was 0.002mm across the data set. Fifty-five biocomposite anchors (43.6%) showed an increased tunnel diameter of greater than 0.1mm compared to anchor size. 7 PEEK anchors (41%) demonstrated an increased tunnel diameter greater than 0.1mm. Additionally, 14 tunnels demonstrated an increased width greater than 1mm compared to anchor size and all were biocomposite anchors. There was no difference in tunnel widening between biocomposite and PEEK anchors (p=0.34). The average change in width across widened tunnels was 0.07mm. The average change in tunnel size across all anchors was 0.02mm. On univariate analysis, bone mineral density, anchor size, anchor position, time to CT scan, composition, and age were not shown to have a statistically significant correlation. Conclusion: At short term 2 year follow-up there was no difference in tunnel widening between PEEK and biocomposite suture anchors. Although the majority of bone tunnels did not demonstrate significant widening compared to the implant size, 43.6% of biocomposite and 41% PEEK anchors generated reactive changes greater than 0.1mm. There were no clear trends in anchor type or location that clearly contributed to tunnel widening.